Analisis Dampak Game Online Terhadap Perubahan Karakter - Anggraeni, Rita; Nurharini, Atip; Budiarso, Yunita Sari; Putri, Linda Amelia; Gumelar, Cahyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine the impact of online games on character changes in children with research methods using qualitative methods with data collection techniques in the form of interviews and questionnaires. The author found that the impact of this online game can change the attitude or character of students from being diligent to being more lazy, children also do not respond to their parents' calls when parents ask their children for help. However, the parenting style of the parents influences changes in the child's attitude and character. When parents limit the hours they use gadgets, there are not many changes experienced by children, they are still willing to learn.